2010
DOI: 10.1016/j.otohns.2010.01.029
|View full text |Cite
|
Sign up to set email alerts
|

Post‐tonsillectomy bleeding in children with von Willebrand disease: A single‐institution experience

Abstract: Objectives-1) Compare rates of post-tonsillectomy bleeding in pediatric patients with and without von Willebrand disease (vWD).2) Identify factors that may increase the risk for posttonsillectomy bleeding in children with and without vWD.Study Design-Historical cohort study.Setting-Tertiary care, university-based pediatric hospital.Subjects and Methods-Medical records were examined for 99 patients with vWD and 99 patients without vWD under the age of 18 years who underwent tonsillectomy with or without adenoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 23 publications
(108 reference statements)
2
28
0
1
Order By: Relevance
“…A recent report by Venkatesan et al [5] found no increased risk of POH in a cohort of 14 patients with haematological abnormalities (red blood cell, platelet, or coagulation disorders) similar to the report by Rodriguez et al [6] who studied 99 patients with vWD. A recent report by Venkatesan et al [5] found no increased risk of POH in a cohort of 14 patients with haematological abnormalities (red blood cell, platelet, or coagulation disorders) similar to the report by Rodriguez et al [6] who studied 99 patients with vWD.…”
Section: Discussionsupporting
confidence: 70%
“…A recent report by Venkatesan et al [5] found no increased risk of POH in a cohort of 14 patients with haematological abnormalities (red blood cell, platelet, or coagulation disorders) similar to the report by Rodriguez et al [6] who studied 99 patients with vWD. A recent report by Venkatesan et al [5] found no increased risk of POH in a cohort of 14 patients with haematological abnormalities (red blood cell, platelet, or coagulation disorders) similar to the report by Rodriguez et al [6] who studied 99 patients with vWD.…”
Section: Discussionsupporting
confidence: 70%
“…Finally, Rodriguez et al. [8] compared the rates of post‐tonsillectomy bleeding in 198 paediatric patients with or without VWD. A single preoperative dose of DDAVP was administered to 90/99 (91%) VWD patients, (70% with type 1), among whom 46/99 received EACA for an unspecified postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 It is thus one of the most commonly performed surgical procedures. 3 In particular, tonsillectomy and/or adenoidectomy is the most common elective surgical procedure among US children, being performed in 300 000 patients every year.…”
Section: Introductionmentioning
confidence: 99%